2014
DOI: 10.1111/jace.13217
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and Temperature Dependent Electrical Properties of Er‐Doped 0.94Bi0.5Na0.5TiO3‐0.06BaTiO3 Ceramics

Abstract: Er-doped 0.94Bi 0.5 Na 0.5 TiO 3 -0.06BaTiO 3 (BNT-6BT: xEr, x is the molar ratio of Er 3+ doping) lead-free piezoceramics with x = 0-0.02 were prepared and their multifunctional properties have been comprehensively investigated. Our results show that Er-doping has significant effects on morphology of grain, photoluminescence, dielectric, and ferroelectric properties of the ceramics. At room temperature, the green (550 nm) and red (670 nm) emissions are enhanced by Er-doping, reaching the strongest emission in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Pure BNT is difficult for poling because of its large coercive field ( E c = 73 kV/cm) and high conductivity . To improve electrical properties, a number of BNT‐based ceramics have been studied extensively, such as BNT‐BaTiO 3 , BNT‐BaTiO 3 ‐BaZrO 3 , BNT‐BaTiO 3 ‐Er 2 O 3 , BNT‐BaTiO 3 ‐K 0.5 Na 0.5 Nb 0.5 , BNT‐Bi 0.5 K 0.5 TiO 3 , BNT‐Bi 0.5 K 0.5 TiO 3 ‐BiAlO 3 , BNT‐Bi 0.5 K 0.5 TiO 3 ‐K 0.5 Na 0.5 NbO 3 , BNT‐MnO 2 , BNT‐SrTiO 3 , and so on. Among them, (1− x )BNT‐ x BaTiO 3 ‐based ceramics show a rhombohedral–tetragonal morphotropic phase boundary at x = 0.06–0.07 and demonstrate improved electrical properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure BNT is difficult for poling because of its large coercive field ( E c = 73 kV/cm) and high conductivity . To improve electrical properties, a number of BNT‐based ceramics have been studied extensively, such as BNT‐BaTiO 3 , BNT‐BaTiO 3 ‐BaZrO 3 , BNT‐BaTiO 3 ‐Er 2 O 3 , BNT‐BaTiO 3 ‐K 0.5 Na 0.5 Nb 0.5 , BNT‐Bi 0.5 K 0.5 TiO 3 , BNT‐Bi 0.5 K 0.5 TiO 3 ‐BiAlO 3 , BNT‐Bi 0.5 K 0.5 TiO 3 ‐K 0.5 Na 0.5 NbO 3 , BNT‐MnO 2 , BNT‐SrTiO 3 , and so on. Among them, (1− x )BNT‐ x BaTiO 3 ‐based ceramics show a rhombohedral–tetragonal morphotropic phase boundary at x = 0.06–0.07 and demonstrate improved electrical properties …”
Section: Introductionmentioning
confidence: 99%
“…Among them, (1Àx)BNT-xBaTiO 3 -based ceramics show a rhombohedral-tetragonal morphotropic phase bound-ary at x = 0.06-0.07 and demonstrate improved electrical properties. [4][5][6][7][8][9] Electrical properties of BNT-based materials are closely related to the deviation of Na + and Bi 3+ from chemical stoichiometry. Sung et al found that effects of Bi 3+ nonstoichiometry on dielectric and piezoelectric properties of the BNT ceramics are different from that of Na nonstoichiometry.…”
Section: Introductionmentioning
confidence: 99%